Coming to Terms With Living Shorelines: A Scoping Review of Novel Restoration Strategies for Shoreline Protection - Smith, Carter S.; Rudd, Morgan E.; Gittman, Rachel K.; Melvin, Emily C.; Patterson, Virginia S.; Renzi, Julianna J.; Wellman, Emory H.; Silliman, Brian R. (Frontiers in Marine Science, 2020)
In an era of rapid coastal population expansion and habitat degradation, restoration is becoming an increasingly important strategy for combating coastal habitat loss and maintaining ecosystem services. In particular, techniques that use habitat restoration alone or restoration in combination with built infrastructure to provide coastal protective services are growing in popularity. These novel approaches, often called living shorelines, have the potential to expand the reach and applicability of coastal restoration projects. To understand how living shorelines research has expanded over time, we conducted a scoping review of English-language peer-reviewed articles. We included papers that self-identified as living shorelines research, as well as studies that used other related terminology, to investigate trends in publication rates, geography, site characteristics, and outcomes measured. Using a systematic search protocol, we compiled a database of 46 papers; the earliest study was published in 1981, and the earliest study to use the term living shoreline was published in 2008. Eighty-three percent of studies were conducted in North America, followed by 11% in Asia, and 7% in Europe, but the use of the term living shoreline was almost exclusively restricted to North America. Saltmarshes, oyster reefs, mangroves, and freshwater vegetation were used in living shoreline designs, but 91% of studies also incorporated structural materials like oyster shell and rock. Most living shorelines research was conducted at sites that were less than five years old. The vast majority of studies exclusively reported on ecological outcomes (89%), and of those, ecological processes were measured in 74% of studies. Processes related to coastal protection were measured most frequently (52% of ecological studies), followed by biological interactions, water filtration, nutrient cycling, and carbon sequestration. All together, our data suggest that living shorelines research is on the rise, but there is a need for more long-term data, socio-economic research, further consensus on the terminology used to describe different types of projects, and research on the types of living shorelines that are most effective in different environmental contexts. Future long-term and interdisciplinary research will help to elucidate the full effects of living shorelines.